EFEKTIFITAS PENYULUHAN DALAM MENINGKATKAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA PADA MASA NIFAS DI PUSKESMAS RAMBAH - Martha, Oci Yuliana; Nurkhasanah, Siti; Aldriana, Nana (AHM Center, 2023)
Nutritional anemia is a health problem that plays a role in causing high maternal mortality rates, infant mortality rates and low work productivity, sports achievements and learning abilities. Therefore, tackling nutritional anemia is a potential program to improve the quality of human resources. The purpose of this study was to determine the effectiveness of counseling in increasing pregnant women's knowledge about anemia during the puerperium. This research method is quantitative analytic with the research design used is pre-experimental with one group pre-test and post-test design. Data collection used a questionnaire, while data analysis used the T-Dependent test. The sample in this study was 56 pregnant women. The results of the research from data analysis mean that prior knowledge is 15.54, knowledge after is 96.79. The mean difference before and after being given counseling was 81.25. The results of the statistical test obtained a value of p = 0.00, which means that there is an effect of counseling to increase pregnant women's knowledge about anemia during the puerperium. It is hoped that the puskesmas will provide information through counseling on anemia material in adolescence to the postpartum period